Delayed Presentation of Traumatic Diaphragmatic Rupture with Herniation of the Left Kidney and Bowel Loops - Amiya Kumar Dwari; Abhijit Mandal; Sibes Kumar Das; Sudhansu Sarkar (Case Reports in Pulmonology)
Rupture of the diaphragm mostly occurs following major trauma. We report a case of delayed presentation of traumatic diaphragmatic hernia on the left side in a 44-year-old male who presented two weeks after a minor blunt trauma. Left kidney and intestinals coils were found to herniate through the diaphragmatic tear. This case demonstrates the importance of considering the diagnosis in all cases of blunt trauma of the trunk. It also illustrates the rare possibility of herniation of kidney through the diaphragmatic tear.